Comparative study between backstepping and backstepping sliding mode controller for suspension of vehicle with a magneto-rheological damper - Mohamed Belkacem; Kadda Zemalache Meguenni; Ismail Khalil Bousserhane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The Suspensions are among the important components of vehicles, providing comfort for passengers and protecting the chassis and freight. They are normally provided with dampers that mitigate these harmful and uncomfortable vibrations. This work aims at investigating the potential of the use of the Magnetorheological Damper as a semi-active suspension for passenger vehicles to improve their ride dynamics and to, ensure their manipulability, and reduce unwanted vibrations levels. To achieve desired performances, a hybrid controller based on a backstepping-sliding mode control strategy is derived to increase the dynamic performance of the automotive suspension component and providing comfortable passenger traveling. Numerical simulation is used to test the efficiency of the proposed controller. The obtained results show that the proposed backstepping sliding mode controller is more efficient and robust against road profile excitation and external disturbances in comparison to a classical controller based on backstepping and sliding mode control.